Tau nuclear translocation is a leading step in tau pathology process through P53 stabilization and nucleolar dispersion. Issue 4 (15th February 2022) - Roqanian, Shaqayeq; Ahmadian, Shahin; Nabavi, Seyed Masood; Pakdaman, Hossein; Shafiezadeh, Mahshid; Goudarzi, Ghazaleh; Shahpasand, Koorosh
Abstract: Tau protein abnormalities are associated with various neurodegenerative disorders, including Alzheimer's disease (AD) and traumatic brain injury (TBI). In tau‐overexpressing SHSY5Y cells and iPSC‐derived neuron models of frontotemporal dementia (FTD), axonal tau translocates into the nuclear compartment, resulting in neuronal dysfunction. Despite extensive research, the mechanisms by which tau translocation results in neurodegeneration remain elusive thus far. We studied the nuclear displacement of different P‐tau species [ Cis phosphorylated Thr231‐tau ( cis P‐tau), phosphorylated Ser202/Thr205‐tau (AT8 P‐tau), and phosphorylated Thr212/Ser214‐tau (AT100 P‐tau)] at various time points using starvation in primary cortical neurons and single severe TBI (ssTBI) in male mouse cerebral cortices as tauopathy models. While all P‐tau species translocated into the somatodendritic compartment in response to stress, cis P‐tau did so more rapidly than the other species. Notably, nuclear localization of P‐tau was associated with p53 apoptotic stabilization and nucleolar stress, both of which resulted in neurodegeneration. In summary, our findings indicate that P‐tau nuclear translocation results in p53‐dependent apoptosis and nucleolar dispersion, which is consistent with neurodegeneration. Abstract : P53 is typically degraded by proteasomes, with Mdm2 playing a significant role. Under tauopathy stress, pathogenic P‐tau ( cis P‐tau, AT8, and AT100 P‐tau) are formed in the neurites. They gradually moved from the neurites into the soma and nucleus. P‐tau nuclear mislocalization is accompanied by p53 stabilization, bax, and cleaved caspase‐3 formation, and significant nucleolar dispersion, ultimately leading to neuron death. Cis Pt, Cis P‐tau; AT8, AT8 P‐tau; AT100, AT100 P‐tau; CBax, cleaved bax; CCasp3, cleaved caspase‐3; Cytoc, Cytochrome c.